2016
DOI: 10.1038/srep39140
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid microscaffold-based 3D bioprinting of multi-cellular constructs with high compressive strength: A new biofabrication strategy

Abstract: A hybrid 3D bioprinting approach using porous microscaffolds and extrusion-based printing method is presented. Bioink constitutes of cell-laden poly(D,L-lactic-co-glycolic acid) (PLGA) porous microspheres with thin encapsulation of agarose-collagen composite hydrogel (AC hydrogel). Highly porous microspheres enable cells to adhere and proliferate before printing. Meanwhile, AC hydrogel allows a smooth delivery of cell-laden microspheres (CLMs), with immediate gelation of construct upon printing on cold build p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 56 publications
(72 reference statements)
0
85
0
Order By: Relevance
“…Levato et al (2014) developed an alternative approach by combining bioprinting with microcarrier technology, which allowed extensive expansion of cells on cell-laden PLA-based microcarriers. Tan et al (2016) used poly( d , l -lactic-co-glycolic acid) porous microspheres enabling cells to adhere and proliferate before printing.…”
Section: Currently Available Bioinksmentioning
confidence: 99%
“…Levato et al (2014) developed an alternative approach by combining bioprinting with microcarrier technology, which allowed extensive expansion of cells on cell-laden PLA-based microcarriers. Tan et al (2016) used poly( d , l -lactic-co-glycolic acid) porous microspheres enabling cells to adhere and proliferate before printing.…”
Section: Currently Available Bioinksmentioning
confidence: 99%
“…Collagen has also been used as part of mixed polymer systems such as collagen/alginate/gelatin for the proliferation of human corneal epithelial cells [257]; collagen with sodium alginate for the proliferation and gene expression of chondrocytes for cartilage tissue engineering [299]; collagen microfibers within a gelatin methacrylate (GelMA) matrix as well as collagen/agarose for the viability, spreading, and differentiation into osteocytes of bone mesenchymal stem cells [300][301][302]; and collagen/hyaluronic acid for 3D liver microenvironments containing primary human hepatocytes and liver stellate cells [209].…”
Section: Biocompatibility Biodegradability and Bioactivitymentioning
confidence: 99%
“…Inclusion of genipin, feature size 400 ”m, compressive E: 17 kPa to 1.4 MPa [295] Indirect coating of collagen onto TPP scaffold, feature size 30 ”m [290] Osteoblast cells, human adipose stem cells [295]; tissue spheroids [296]; keratinocytes and fibroblasts [297], hMSCs [298]; human corneal epithelial cells [257]; osteocytes [300][301][302]; 3D liver microenvironments [209] Fibrin (4.4.2) Mixed with PVA, feature size 100 ”m [303] Indirect methods of coating [306], micro-molding with feature size 20 ”m [61] Bone marrow stromal cells [307]; neural tissue [308]; dental pulp stem cells [309]; Schwann cells [219,303]; human umbilical vein endothelial cells, hMSCs [310] Gelatin (4.4.3)…”
Section: ) Applicationsmentioning
confidence: 99%
“…Because bioprinting mostly employs hydrogels, which possess drastically weaker mechanical properties than native bone, additives are added to increase the mechanical strength and stiffness of these printable hydrogels. Such hybrid‐tissue engineered constructs are generally composed of a combination of rigid, porous additives that maintain structural and mechanical integrity of hard tissues, with relatively softer hydrogels for supporting biological factors (Figure ; Jariwala et al, ; Levato et al, ; Tan, Tan, Yeong, & Tor, ). Several studies have reported the development of novel 3D bioprinted materials for promoting bone regeneration such as incorporation of robust PCL framework to encapsulate Ca/polyphosphate microparticles (Neufurth et al, ) and conjugating it with thermo‐sensitive chitosan (Dong, Wang, Zhao, Zhu, & Yu, ), alginate‐polyvinyl alcohol with HA (Bendtsen et al, ).…”
Section: D Bioprintingmentioning
confidence: 99%